Evaluation of Mineral Contents in Milk of Dairy Cattle Fed Elephant Grass Planted at Ex-Coal Mining Land - H. Harmini; D. Evvyernie; P. D. M. H. Karti; Y. Widiawati (Faculty of Animal Science, Bogor Agricultural University, 2020)
The growth of several types of grass in the area of ​​mine re-vegetation is rapidly providing an opportunity to be used as forages despite the possibility of heavy metal contamination. The purpose of the study was to evaluate the effect of treatment of different levels of elephant grass (EG) (Pennisetum purpureum) planted at ex-coal mining reclamation on milk productivity and mineral contents of dairy cattle. This study used four lactating (second lactation) dairy cattle using Latin Square Design of 4 (treatments) x 4 (replications). Each period was 21 days consisted of 14 days of preliminary for feed adaptation and 7 days for observation. Treatments were P0 (0% ex-coal mining (EEG)+60% Farmer’s EG (FEG)+40% Concentrate), P1 (15% EEG+45% FEG+40% Concentrate), P2 (30% EEG+30% FEG+40% Concentrate), and P3 (60% EEG+0% FEG+40% Concentrate). The study observed variables of feed intake and efficiencies, milk production, milk quality, and mineral contents of milk. Results showed that EEG treatment at different levels did not affect fresh and dry matter intake. The highest fresh and dry matter intake was found in P0 treatment. There was no significant difference in giving EG planted at the ex-coal mining and the farmer’s land on the milk production and milk quality. The only significant differences (p<0.05) were found in mineral Fe and Mg contents of milk. The study concluded that giving EG planted at the ex-coal mining area until 60% of forage affected Fe and Mg contents of milk, but they are still in the safe limit.